OP0055 Immunochip Validation Study Confirms Two Novel RA Susceptibility Loci, BACH2 and RAD51L1. (23rd January 2014) - McAllister, K.; Eyre, S.; Bowes, J.; Plenge, R.; Greenburg, J.; Pappas, D.; Worthington, J.; ,
Abstract : Background: Rheumatoid arthritis (RA) is a complex, chronic autoimmune disease affecting approximately 1% of the adult population worldwide. A recent large scale genetic fine-mapping study, Immunochip (IC) and combined analysis with RA genome wide association (GWAS) data, identified 14 novel loci associated with RA bringing the total number of susceptibility loci in Caucasians to 46. In addition to the confirmed loci, the study provided evidence for 16 SNPs putatively associated with RA in the next tier of significance (P=6×10 -05 <5×10 -08 ), either in an unstratified analysis or with anti-cyclic citrullinated peptide antibody (ACPA) positive/negative subgroups. We undertook a validation study of these SNPs in independent RA cases (6, 106) and controls (4, 290), to determine their association with RA. Objectives: To validate genomic variants implicated in the IC study at suggestive levels of significance (P=6×10 -05 <5×10 -08 ) with RA. Methods: A total of 16 SNPs were selected for genotyping. Samples (6, 106 RA cases and 4, 290 controls) for the validation study were from two sources: (i) The UKRAGG (UK Rheumatoid Arthritis Genetics Group) collection with 3900 RA patients and 2427 controls recruited from 6 centres across the UK and (ii) The U.S. Consortium of Rheumatology Researchers of North America (CORRONA) collection and i2b2 program (2206 cases and 1863 controls). Association analyses were performed both separately on the validation data and in a meta-analysis with the original IC cases and controls comprising a total of 17, 581 cases and 20, 160 controls. Additionally stratified analysis was performed on ACPA subsets. Results: 5 SNPs had evidence of association in the validation samples (p=<0.05), however following combined analysis with IC data only 2 reached genome wide significance. One SNP, rs72928038 mapping to an intron of BACH2 was significantly associated (p=1.19×10 -08, OR 1.12) and a second SNP, rs911263 mapping to an intron of RAD51L1, was significantly associated in the ACPA positive subgroup analysis (p=4.06×10 -08, OR 0.89), confirming them as true RA susceptibility loci in Caucasians. Conclusions: We have a detected association to SNPs mapping to the genes for BACH2, and RAD51L1 with RA at genome wide-significance levels (p=<5×10 -08 ), taking the number of confirmed RA loci to 48 in Caucasians. BACH2 is involved in the B cell differentiation pathway and RAD51L1 in a DNA repair pathway making them both strong biological candidate genes in autoimmunity. This study illustrates that further increasing the sample sizes of case control association studies beyond those used in the combined analysis of RA IC and GWAS data, has the potential to reveal additional RA susceptibility markers. Identification of additional genetic variants that predispose to RA will enhance our capacity to elucidate the molecular mechanisms and biological pathways that are important in RA pathogenesis. References: Eyre, S., Bowes, J., Diogo, D., Lee, A., Barton, A., Martin, P. et al. (2012). High-density genetic mapping identifies new susceptibility loci for rheumatoid arthritis. Nat Genet, 44, (12), 1336-1340. Disclosure of Interest: None Declared